The pandemic consumer response: a stockpiling perspective and shopping channel preferences - Papagiannidis, Savvas; Alamanos, Eleftherios; Bourlakis, Michael; Dennis, Charles (Wiley, 2022)
Covid-19 has changed consumer behaviour, probably forever. Initial consumer stockpiling led to stockouts, threat and uncertainty for consumers. To overcome shortages, consumers expanded their use of channels and many consumers started buying online for the first time. In this paper, we aim to address important research gaps related to consumer behaviour during the pandemic and especially stockpiling. Our paper starts by presenting the findings of our pre-study, which used social media to elicit or confirm potential constructs for our quantitative models. These constructs complemented the protection motivations theory to explain stockpiling behaviour, forming the basis for study 1, the stockpiling preparation stage and study 2, the effects of the Covid-19 pandemic disruptor on customer service logistics and lockdown shopping channel preferences. For studies 1 and 2 we gathered data via a UK online panel-structured questionnaire survey (n = 603). Results confirm that consumer-driven changes to supply chains emanate largely from consumer uncertainty. Lockdown restrictions led to consumers feeling socially excluded, but enhanced consumers’ positive attitudes towards shopping online and increased consumers’ altruism. In response, consumers stockpiled by visiting physical stores and/or ordering online. Lockdown restrictions led to feelings of social exclusion but, importantly, stockpiling helped to minimize consumer anxiety and fear and even increase wellbeing.
Keywords: consumer behaviour; supply chain; stockpiling; wellbeing; social exclusion